1D Copper(II)-Aroylhydrazone Coordination Polymers: Magnetic Properties and Microwave Assisted Oxidation of a Secondary Alcohol - Sutradhar, Manas; Alegria, Elisabete C. B. A.; Barman, Tannistha Roy; Guedes da Silva, M. Fátima C.; Liu, Cai-Ming; Pombeiro, Armando J. L. (Frontiers in Chemistry, 2020)
The Cu(II) 1D coordination polymers [Cu3(L1)(NO3)4(H2O)2]n (1) and [Cu2(H2L2)(NO3)(H2O)2]n(NO3)n (2) have been synthesized using the aroylhyrazone Schiff bases N'1,N'2-bis(pyridin-2-ylmethylene)oxalohydrazide (H2L1) and N'1,N'3-bis(2-hydroxybenzylidene)malonohydrazide (H4L2), respectively. They have been characterized by elemental analysis, infrared (IR) spectroscopy, electrospray ionisation mass spectrometry (ESI-MS), single crystal X-ray diffraction and variable temperature magnetic susceptibility measurements. The ligand (L1)2 coordinates in the iminol form in 1, whereas the amide coordination is observed for (H2L2)2 in 2. In 1 the antiferromagnetic interaction through the N-N bridge is stronger than via the oxamide bridge. A weak antiferromagnetic interaction occurs in 2. The catalytic activity of 1 and 2 has been screened towards the solvent-free microwave-assisted oxidation of a secondary alcohol (1-phenylethanol used as model substrate). At 120 °C and in the presence of the nitroxyl radical 2,2,6,6-tetramethylpiperydil-1-oxyl (TEMPO), the complete conversion of 1-phenylethanol into acetophenone occurs with TOFs up to 1200 h-1.